2019
DOI: 10.1080/00103624.2019.1614605
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Rice Yield Under Salinity Stress Using K/Na Ratio Variable in Plant Tissue

Abstract: Estimation of yield reduction in crop caused by the salinity stress is mostly based on variations of soil electrical conductivity and the severity of water stress. Crop response curves to salinity were developed without considering ion toxicity and nutritional imbalance in the plant. The objective of this study was to explore the possibility of using the ratio of the concentration of potassium by sodium in rice leaf (leaf-K/Na) to predict yield under the salinity stress. The rice (Oryza sativa L.) yield under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…For example, K contributed to anther dehiscence and pollen imbibition in rice [ 71 , 72 ]. Decrease of the K/Na ratio is commonly reported as symptomatic of salinity stress [ 73 ]. Surprisingly, we observed that the K/Na ratio is more important in the inflorescences of S. lycopersicum than in those of S. chilense , even at high NaCl concentration.…”
Section: Discussionmentioning
confidence: 99%
“…For example, K contributed to anther dehiscence and pollen imbibition in rice [ 71 , 72 ]. Decrease of the K/Na ratio is commonly reported as symptomatic of salinity stress [ 73 ]. Surprisingly, we observed that the K/Na ratio is more important in the inflorescences of S. lycopersicum than in those of S. chilense , even at high NaCl concentration.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, sodium exclusion is a common natural feature in most plants (Munns, 2005) and can be considered as a key mechanism for high Na + level (sodicity) tolerance (Genc et al, 2016). Moreover, salt-induced yield reduction has been correlated with K + /Na + in plant tissues in several studies (Chunthaburee et al, 2016;Reddy et al, 2017) and leaf K + /Na + was even suggested as a tool to predict rice yield under saline conditions (Mel et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Soil salinity is one of the most important abiotic stress factors directly limiting plant yield in agricultural production areas of all over the world (Shokat and Großkinsky 2019). Plants respond to salts in soil or in irrigation water at different levels by tuning complex physiological and molecular mechanisms (Mel et al 2019). High salt prevents the water uptake and creates a physiological drought (Khayamim et al 2014) or ion toxicity to the embryo of seeds, which directly limits fast and even seed germination (Farooq et al 2017).…”
Section: Introductionmentioning
confidence: 99%